Ibuisme Masa Kini: Suatu Etnografi tentang Posyandu dan Ibu Rumah Tangga - Wicaksono, Mochammad Arief (UMBARA Indonesian Journal of Anthropology, 2016)
"Housewife" is often an issues and concepts essential to studies the relationship between the state and society at the micro level. Through the women in the villages of cities, the "face" of state trying to be presented continuously in everyday life, one of them in public health system through Posyandu (Pos Pelayanan Keluarga Berencana dan Kesehatan Terpadu). Posyandu put women, especially housewifes, as the âspearheadâ for realizing a healthy society, both in terms of physical and everyday behavior. The housewife is not only a target of health programs, but also as the person running the program, called Kader Posyandu. Each month the cadre pf Posyandu should attend the meetings, held events medical examinations for infants and the elderly, health counseling, surveys to homes, and making health data in the village, which of course it is all done in tandem with their role as housewifes and partly again also has another job outside the home. This study illustrates how the state wants to stick around to be present at the local level people today, especially in health programs through the perspective housewife-Posyandu cadres who are willing to work for the country. This study also wanted to answer the question, what is the reason for the housewifes so that it would work for the state in the present context. Observation and in-depth interviews with the cadres Posyandu conducted to answer the research questions above. Many of them on behalf of volunteerism in running this program, through this article we will know how the state can instill a sense of volunteerism so that the ideals of a healthy society can be realized through the role of women, especially housewifes.